2018
DOI: 10.1097/mao.0000000000001753
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond Infrared Laser (PIRL) Application in Stapes Surgery—First Experience in Human Temporal Bones

Abstract: Objective:Using a contact-free laser technique for stapedotomy reduces the risk of mechanical damage of the stapes footplate. However, the risk of inner ear dysfunction due to thermal, acoustic, or direct damage has still not been solved. The objective of this study was to describe the first experiences in footplate perforation in cadaver tissue performed by the novel Picosecond-Infrared-Laser (PIRL), allowing a tissue preserving ablation.Patients and Intervention:Three human cadaver stapes were perforated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Automatic focusing can be considered a requirement for any practical use of the laser in an operating theater. It can be achieved either by a suitable auto‐focus system, as in our study, or by guiding the laser through a fiber, which is held by the hand of the surgeon and brought into direct contact with the tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Automatic focusing can be considered a requirement for any practical use of the laser in an operating theater. It can be achieved either by a suitable auto‐focus system, as in our study, or by guiding the laser through a fiber, which is held by the hand of the surgeon and brought into direct contact with the tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Current developments of a flexible applicator should take this clinical requirement into account (75). Initial results have shown that multimode fiber can provide lossless energy transfer of PIRL to difficult-toreach objects (76).…”
Section: Comparison Of Dental Root Preparation With Osteotomies By Pirlmentioning
confidence: 99%
“…Most importantly, this work discovered the essential physics to strongly drive the phase transitions involved in laser ablation faster than nucleation growth. The new insight into how to arrest nucleation growth provided the long sought solution to the problem of cavitation and shock wave damage in laser surgery, to provide the first tool capable of scar-free surgery at the fundamental (single cell) limit to minimally invasive surgery and with complete biomarkers for surgical guidance. , These discoveries give testimony to the importance of atomically resolved dynamics not only for its deeper level of understanding of the structural dynamics of matter, but also for the enormous applications that will be forthcoming from such knowledge.…”
Section: Space-time Limits To Imaging Chemistry: Classical Casementioning
confidence: 99%